The motivation behind Egyptian youth subscription to video on demand services and excessive use: a case study on WATCH iT! - Aya Alaa Eldin Abdel Fattah; Lamiaa Shehata; Sofia Zohir Moustafa Kamel (Insights into Language, Culture and Communication)
With the rising competition in the subscription video on demand (SVoD) services market, the services’ providers are trying to elevate the services they offer. In this context, this study aims to explore the individuals’ psychological factors, motives, perceived ease of use, and perceived usefulness that influence the video streaming platforms usage behavior and lead to excessive usage by their users. This research has adapted key measures from the “technology acceptance model” (TAM) and from the “uses and gratifications theory” (UGT) to better understand the effects of the users’ psychological factors, instrumental and ritualized motivations on their excessive usage of the platform WATCH iT!. An online questionnaire was distributed and data was gathered from 350 respondents with age range between 16-39. Low self-esteem and lack of self-control were negatively related to the excessive use behavior identified in this study. This study suggests that entertainment uses and gratification is a strong predictor of excessive use of the platform WATCH iT!. Evidently, information seeking did not predict the excessive use of the platform. Moreover, the individuals’ perceived usefulness and ease of use were significant antecedents of the excessive use the platform. This study contributes to the academic literature by generating new knowledge about the individuals’ background characteristics and motivations that explain the excessive use behavior of the platform WATCH iT!. The findings imply that there is scope for the providers of online streaming services to improve their customer- centric marketing by refining their content creation to attract viewers and garner their loyalty. This study integrates the TAM and UGT frameworks to better understand the effects of the users’ psychological factors, instrumental and ritualized motivation on their excessive watching of movies and series through the platform WATCH iT!.   Received: 07 May 2024 Accepted: 30 July 2024 Published: 19 August 2024